LEASING IN THE WESTERN BALKANS AND THE FALL OF THE AUSTRIAN HYPO-ALPE-ADRIA BANK - Tajti, Tibor (Pravni zapisi, 2018)
The hybrid contract known in Continental Europe as leasing has arrived to the Balkans and other post-socialist countries of Europe from the United States yet with the intermediation of various Western European jurisdictions that have reshaped the contours of the newcomer transaction to fit the context. Western European banks expanding to the region then brought with them their home country perceptions. This resulted in significantly differing leasing laws in the region. Although the process began already before the 1980s, one could speak of real expansion only from the 1990s on. By now leasing has become an important part of most jurisdictions of the region. Notwithstanding the organic growth, the article posits, leasing is still not properly understood, the regulations suffer from gaps and are inappropriate to boost the local leasing industries. This is readily proved by most recent reports of some international organizations. Especially small and mid-scale enterprises suffer as equipment leasing remains underdeveloped, what is a major systemic defect as bank credit is (as well) unavailable to them. The article aims to identify and comment those common deficiencies of the leasing laws of this niche of Europe that have so far been neglected yet the tackling of which is inevitable to boost the local industries. This is done, first, by sketching the experiences with and the judicial responses to a few unreported first generation leasing cases from Vojvodina (Serbia) from the end of the 1980s to determine what main problems the lessor faced in implementing their leasing transactions. It is claimed that some of the key problems have not been eliminated from the legal system ever since, in particular the problems with repossession upon default. Secondly, comparative law is as well resorted to yet contrary to European approaches with more insight into the solutions of the United States as the jurisdiction wherefrom leasing originates. The final part then comments those key problems and dilemmas that still hinder the proper development of the local leasing industries yet which have been largely bypassed. These are the 1/ problems caused by uncritically taken over solutions and definitions, 2/ the lack of legal tools for prompt repossession of the object of leasing, 3/ the conceptual confusion related to what in common law is known as the ‘election of remedies doctrine’, as well as 4/ the incomprehension of the importance of the policy choices justifying the recognition and judicial support for the so-called hell-or-high-water clauses. The article additionally posits that the very same reasons might have generated the problematic leasing portfolios of the Austrian Hypo-Alpe-Adria Bank and therefore might have also contributed to the eventual fall of the Bank. In the lack of empirical evidences and other firm evidences, however, this position should not be taken to be more than a question to be answered in the future, if for nothing else, then for having some satisfactory answers for the fall of the Bank and for the sake of better understanding leasing. Key words: leasing (operating, financial), equipment leasing, bank bailout, self-help repossession, legal engineering, small and mid-scale enterprise (SME) financing, law reforms.